Analyzing the impact of nurses emotional intelligence on patients quality of care with the mediating role of job involvement - Mohd Sadad, Mahmud; Irfan, Sabir; Azhar, Tanveer (2020)
The aim of the current study was to analyze the impact of Nurses Emotional Intelligence on Patients Quality-of-Care with the mediating role of Job Involvement. Deductive approach was used to study the constructs, derived from theory. Research hypotheses are formulated from existing theory and knowledge relating to emotional intelligence and patientscentered care. The sample was calculated through an online calculator ”Raosoft”. The recommended final simple size was 292 with a population size of 1200 at 95% confidence level, 5% error of margin and 50% response distribution. Correlations and regression analysis were performed to measure the mediation analysis. The statistical outcomes confirmed nurses emotional intelligence positively affects patients quality of care. Furthermore, the association between emotional intelligence and job involvement and job involvement and patients quality of care are also positive. Job involvement has a partial mediation impact in the said association. The study concludes by discussing future research directions.